2009
DOI: 10.1007/s00425-009-1024-1
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin expression and localization in plant cells during pollen–pistil interactions

Abstract: In this report, the distributions of calreticulin (CRT) and its transcripts in Haemanthus pollen, pollen tubes, and somatic cells of the hollow pistil were studied. Immunoblot analysis of protein extracts from mature anthers, dry and germinated pollen, growing pollen tubes, and unpollinated/pollinated pistils revealed a strong expression of CRT. Both in vitro and in situ studies confirmed the presence of CRT mRNA and protein in pollen/pollen tubes and somatic cells of the pistil transmitting tract. The co-loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 60 publications
6
37
0
Order By: Relevance
“…Similarly, the transcripts of CRTs are detected in pollen grains, pollen tubes, and pistils in Haemanthus (Lenartowska et al, 2009). Together, these data suggest that POD1 most likely interacts with CRT3 and plays an important role in ER quality control.…”
Section: Pod1 Interacts With Crt3mentioning
confidence: 89%
“…Similarly, the transcripts of CRTs are detected in pollen grains, pollen tubes, and pistils in Haemanthus (Lenartowska et al, 2009). Together, these data suggest that POD1 most likely interacts with CRT3 and plays an important role in ER quality control.…”
Section: Pod1 Interacts With Crt3mentioning
confidence: 89%
“…Additionally, high levels of CRT and its transcripts were detected in developing tobacco anthers, especially in pollen tetrads and in the active tapetum, as well as in dry, hydrated, and germinating pollen and growing tubes (Nardi et al 2006). Finally, we observed strong CRT expression in germinated pollen and elongated tubes of Haemanthus (Lenartowska et al 2009) and Petunia (Lenartowska et al 2001, 2002; Lenartowski et al 2014, 2015). On the basis of our findings, we speculated that CRT is translated on ER-associated ribosomes in germinating pollen and growing tubes.…”
Section: Introductionmentioning
confidence: 63%
“…For example, the ER lumen in Arabidopsis pollen tubes sequesters high levels of Ca 2+ (Iwano et al 2009), and both auto inhibited Ca 2+ ATPases and ER-type Ca 2+ ATPases are present in pollen (see review by Sze et al 2006). Additionally, studies in Petunia (Lenartowska et al 2002; Lenartowski et al 2015), Nicotiana (Nardi et al 2006), and Haemanthus (Lenartowska et al 2009) indicate that the ER of pollen tubes contains CRT, which is a prominent Ca 2+ buffer in eukaryotic cells (see review by Jia et al 2009; Michalak et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Although many regulators of Ca 2+ dynamics and effectors of Ca 2+ signaling have been identified during pollen tube growth regulation, the regulatory mechanism for Ca 2+ in pollination remains to be elucidated. Lenartowska et al (2009) reported that calreticulins, proteins involved in cellular Ca 2+ homeostasis regulation, could be detected in the pollen/pollen tubes and the transmitting tract of pollinated pistil of Haemanthus, suggesting a possible role for these proteins in pollen-pistil interaction. Additionally, reactive oxygen species and nitric oxide (NO) signaling were found to be involved in pollen-stigma interaction, and NO exerts its role by modulating Ca 2+ signaling (McInnis et al, 2006;Hiscock and Allen, 2008;Prado et al, 2008).…”
Section: Stigma Signaling In the Pollen-stigma Interactionmentioning
confidence: 99%